Community-Led Action Research in Oncology: Pandemic-Appropriate Radiotherapy Innovations Evaluated (CLARO PARTE) for Latin America and the Caribbean Countries - Ivy Riano; César Alas-Pineda; Sarahi Reyes Garcia; Raúl Murillo; Francisco Gutiérrez-Delgado; Eduardo Cazap; Celia Maria Pais Viegas; Marcela de la Torre; Kaory C. Barahona; Gustavo J. Sarria; Ramón del Castillo Bahi; Álvaro Luongo-Céspedes; et al. (JCO Global Oncology, 2024)
PURPOSEThis study aimed to identify, evaluate, and rank suitable safety innovations developed during the COVID-19 pandemic in Latin American and Caribbean (LAC) radiation oncology centers.METHODSWe conducted a multimodal participatory engagement collaboration with the Latin-American and Caribbean Society of Medical Oncology. The study consisted of four phases. Innovations were collected from a panel of radiotherapy experts representing a diverse group of 11 countries from LAC (Phase I). Next, a medical scientific team compared the innovations against international standards regarding their potential impact on risk of infection, clinical operation, and continuity of quality cancer care (Phase II). Their findings were supplied to the country representatives who rated the innovations for acceptability in their cancer centers (Phase III), resulting in a final report of the panel's recommendations (Phase IV).RESULTSA total of 81 innovations were reported by the country representatives and merged by the medical scientific team into 24 innovations that combined similar innovations. The 24 innovations were grouped into six categories including practices aimed at (1) reducing clinic crowding (n = 3), (2) increasing screening and vaccinations for COVID-19 disease (n = 5), (3) implementing social distancing (n = 6), (4) strengthening personal infection equipment and disinfection (n = 6), (5) avoiding delaying or shortening treatment protocols (n = 2), and (6) mixed procedures (n = 2). The medical scientific team found nearly all innovations were supported by international recommendations and rated as safe, efficient, and acceptable.CONCLUSIONBy using the lessons learned from the Community-Led Action Research in Oncology: Pandemic-Appropriate Radiotherapy Innovations Evaluated study, a manual of scalable practices in radiation oncology clinics may be developed to guide actions during future large-scale public health crises in low- and middle-income countries of LAC.